Profilin 2 and Endothelial Exosomal Profilin 2 Promote Angiogenesis and Myocardial Infarction Repair in Mice - Li, Zhenkun; Huo, Xueyun; Chen, Keyan; Yang, Fenghua; Tan, Weijiang; Zhang, Qi; Yu, Haixu; Li, Changlong; Zhou, Deshan; Chen, Hao; Zhao, Baoquan; Wang, Yuan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases (CVD) are the leading cause of death worldwide, wherein myocardial infarction (MI) is the most dangerous one. Promoting angiogenesis is a prospective strategy to alleviate MI. Our previous study indicated that profilin 2 (PFN2) may be a novel target associated with angiogenesis. Further results showed higher levels of serum PFN2 and exosomal PFN2 in patients, mice, and pigs with MI. In this study, we explored whether PFN2 and endothelial cell (EC)-derived exosomal PFN2 could increase angiogenesis and be beneficial for the treatment of MI. Serum PFN2, exosomes, and exosomal PFN2 were elevated in rats with MI. PFN2 and exosomes from PFN2-overexpressing ECs (OE-exo) enhanced EC proliferation, migration, and tube formation ability. OE-exo also significantly increased the vessel number in zebrafish and protected the ECs from inflammatory injury. Moreover, OE-exo-treated mice with MI showed improvement in motor ability, ejection fraction, left ventricular shortening fraction, and left ventricular mass, as well as increased vessel numbers in the MI location, and decreased infarction volume. Mechanistically, PI3K might be the upstream regulator of PFN2, while ERK might be the downstream regulator in the PI3K-PFN2-ERK axis. Taken together, our findings demonstrate that PFN2 and exosomal PFN2 promote EC proliferation, migration, and tube formation through the PI3K-PFN2-ERK axis. Exosomal PFN2 may be a valuable target in the repair of MI injury via angiogenesis.